Transcriptome analysis of heterografting on key medicinal compounds accumulation in Ziziphi Spinosae Semen - Xiangrui Fu; Yinfeng Yu; Zikang Lu; Chaohui Wang; Lanping Guo; Yuping Yan; Donglai Ma; Xian Gu (BMC Plant Biology)
Abstract Background Sour jujube (Ziziphus jujuba Mill. var. spinosa (Bunge) Huex H. F. Chou) is a plant of significant dual utility in both food and medicine, with Ziziphi Spinosae Semen (ZSS) referring to its dried mature seed. Homografting and heterografting are the primary methods for sour jujube propagation, but the impact of these grafting techniques on the accumulation of key medicinal compounds and the molecular mechanisms underlying the formation of ZSS remain poorly understood. In this study, we compared homografting (S/S: sour jujube/sour jujube) and heterografting (J/S: gold jujube/sour jujube; D/S: jujube/sour jujube; H/S: huping jujube/sour jujube) in relation to the formation of key medicinal components and the quality of ZSS via HPLC and transcriptomic analyses. Results Entropy weighting analysis revealed that the quality ranking order was J/S > H/S > D/S > S/S, with heterografting significantly increasing the spinosin content in ZSS. Notably, the combination of gold and jujube as rootstocks (J/S) resulted in the highest spinosyn content. Transcriptomic analysis revealed that the differentially expressed genes in heterografting were predominantly involved in aldonic acid metabolism, transmembrane transporter activity, and phosphoenolpyruvate carboxykinase (ATP) activity. KEGG enrichment analysis revealed significant enrichment of the citrate cycle (TCA cycle) and pyruvate metabolism pathways in heterografting. Furthermore, the MYB super family, bZIP family, and C2H2 family are the predominant transcription factor families in ZSS. Conclusions This study enhances understanding of the molecular mechanisms underlying the effects of heterografting on ZSS quality, providing significant implications for the cultivation and improvement of the quality of medicinal ZSS.